Habiling hablon revitalizing the Hablon Weaving Industry and Culture through an exhibit, livelihood training, and weaving center - Barrias, Wynona Caitlin C. (College of Architecture, University of the Philippines Diliman, 2023)
n the Philippines, handloom weaving is an activity which evolved from being a recreational practice to a prominent cottage industry. However, due to its failure to keep up with the rise of industrialization and mass production of factory-produced textiles, it is now considered as a “sunset industry”. Local handloom weaving communities, such as the Hablon weaving communities in Iloilo, have experienced repercussions, and have slowly declined over the years. In recent times, though, there have been various efforts made to revive the industry. To ensure that these initiatives have a lasting impact, architecture can be utilized to further push this agenda. As a place that was once known as a textile capital of the Philippines due to its woven textiles, Iloilo poses itself as a suitable area to promote the revitalization of the local handloom weaving industry. This is especially relevant in the municipality of Miagao, which plays an important role in the practice and revival of Iloilo’s own type of handloom weaving, the Hablon weave. Having this opportunity will allow Miagao to improve its economy and gain recognition locally and globally. By examining the handloom weaving industry and the Hablon weaving communities’ history and culture, an exhibit, livelihood training, and weaving center that seeks to educate people about the industry and empower the communities’ livelihoods will be developed. The development of this facility will be beneficial to the Hablon weavers because it will allow them to safely sustain their source of income and safeguard their cultural heritage. Moreover, this project will also benefit other local handloom weaving industries by acting as a pioneer for more spaces dedicated to promoting and preserving this practice.